The WNT/β-catenin signaling inhibitor XAV939 enhances the elimination of LNCaP and PC-3 prostate cancer cells by prostate cancer patient lymphocytes in vitro - Stakheev, Dmitry; Taborska, Pavla; Strizova, Zuzana; Podrazil, Michal; Bartunkova, Jirina; Smrz, Daniel (Scientific reports, 2019)
Upregulated Wnt/β-catenin signaling is associated with increased cancer cell resistance and cancer cell-elicited immunosuppression. In non-neoplastic immune cells, upregulated Wnt/β-catenin is, however, associated with either immunosuppression or immunostimulation. Therefore, it is difficult to predict the therapeutic impact inhibitors of Wnt/β-catenin signaling will have when combined with cancer immunotherapy. Here, we evaluated the benefit(s) of the Wnt/β-catenin signaling inhibitor XAV939 in the in vitro elimination of LNCaP prostate cancer cells when cocultured with lymphocytes from patients with localized biochemically recurrent prostate cancer (BRPCa). We found that 5 µM XAV939 inhibited β-catenin translocation to the nucleus in LNCaP cells and CD4+ BRPCa lymphocytes without affecting their proliferation and viability. Preconditioning BRPCa lymphocytes with 5 µM XAV939 accelerated the elimination of LNCaP cells during the coculturing. However, during subsequent re-coculturing with fresh LNCaP cells, BRPCa lymphocytes were no longer able to eliminate LNCaP cells unless coculturing and re-coculturing were performed in the presence of 5 µM XAV939. Comparable results were obtained for PC-3 prostate cancer cells. These findings provide a rationale for combining cell-based immunotherapy of PCa with inhibitors of Wnt/β-catenin signaling.
Keywords: Prostatic Neoplasms; nádory prostaty; Humans; tankyrasy; proteiny Wnt; lidé středního věku; T-Lymphocytes; beta-katenin; PC-3 Cells; Aged; Antineoplastic Agents; Wnt Proteins; Tankyrases; senioři; lidé; Immunotherapy; buňky PC-3; Wnt Signaling Pathway; signální dráha Wnt; CD4-Positive T-Lymphocytes; Male; Middle Aged; heterocyklické sloučeniny tricyklické; beta Catenin; nádorové buněčné linie; CD4-pozitivní T-lymfocyty; protinádorové látky; T-lymfocyty; Cell Line, Tumor; mužské pohlaví; imunoterapie; Heterocyclic Compounds, 3-Ring